Refractory hyperactive bladder treated with sacral neuromodulator: case report and literature review - Navarro, Junior J. Araiza J. Araiza; Sánchez, Raúl D. Lara; Uscanga, Oyuki A. Morales; Sosa, María I. Tolentino; Reyes, Fernando López; Vilchis, Jorge A. Barbabosa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
The overactive bladder syndrome is a chronic medical condition that affects the quality of life of patients whether men or women, has a prevalence of 16.5%, however, it is known to increase with age, affecting up to 25% of women older than 65 years and up to 80% in the elderly. More than 90% of cases have no apparent cause. The OAB (Overactive Bladder) It is a condition with characteristic symptoms of urinary urgency, usually accompanied by frequency and nocturia, with or without urge incontinence, in the absence of urinary tract infection or other obvious pathology. The different therapeutic steps are not always sufficient to restore the quality of life.